PREVALENCE AND MOLECULAR CHARACTERIZATION OF MAJOR Culicoides SPECIES FOUND IN SELECTED PARTS OF TAMIL NADU - T. Duraisamy; M. Parthiban; Y. Krishnamohan Reddy; P. Raja; B. Rubinibala; K. Brindha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Culicoides are the biting midges that are involved in the transmission of bluetongue, an economically important disease of small ruminants particularly sheep. The prevalence of Culicoides species in and around sheep farms of selected districts of Tamil Nadu was investigated by setting up UV- LED CDC traps. A total of 1787 specimens of Culicoides were collected, out of which Culicoides imicola was found to be in abundance. The other species included Culicoides oxystoma, Culicoides peregrinus, Culicoides brevitarsis and Culicoides fulvus. It was found that female midges outnumbered the male population in all the identified species. The overall percentage distribution of pigmented, non-pigmented, blood fed and gravid forms were observed to be 25.73%, 25.49%, 38.95% and 9.81% respectively. Morphological identification was complemented by molecular characterization using barcodes obtained by amplification of the mitochondrial eytochrome oxidase gene. The results of BLAST analysis revealed that all the other four species grouped with their respective species clusters except C. oxystoma which showed a higher degree of genetic divergence.